Adaptive Digital Marketing Convergence for Village-Owned Enterprises in Indonesia - Abdurokhim, Abdurokhim; Pujadiaraka, Pandu; Kamila, Puteri; Nurwahid, Arul falah (Jurnal Minds: Manajemen Ide dan Inspirasi, 2026)
Rural enterprises increasingly confront digital exclusion despite mounting pressure to compete in platform-based markets. This study contributes to digital marketing and rural enterprise literature by introducing a staged convergence model integrating content marketing and paid promotion according to varying levels of organizational digital readiness among Village-Owned Enterprises (BUMDES). Using a sequential explanatory mixed-method design, the study combined surveys of 100 BUMDES, interviews, stakeholder discussions, and pilot implementation across five BUMDES in Cirebon Regency, Indonesia. The findings reveal severe limitations in digital literacy, infrastructure, and marketing capacity, yet the proposed convergence model substantially improved online visibility and business performance during implementation. The study demonstrates that digital marketing effectiveness in rural enterprises depends not merely on technological adoption but on adaptive alignment between promotional intensity, organizational capability, and resource constraints. These findings provide practical guidance for policymakers and local governments in designing scalable digital transformation programs for community-based enterprises.